Existence of Positive Periodic Solutions for a Class of n-Species Competition Systems with Impulses - Peilian Guo; Yansheng Liu (International Journal of Differential Equations)
By using the fixed point theorem on cone, some sufficient conditions are obtained on the existence of positive periodic solutions for a class of n-species competition systems with impulses. Meanwhile, we point out that the conclusion of (Yan, 2009) is incorrect.